International Health Regulations (2005) and the U.S. Department of Defense: building core capacities on a foundation of partnership and trust - Blazes David L; Johns Matthew C (BMC, 2010)
Abstract A cornerstone of effective global health surveillance programs is the ability to build systems that identify, track and respond to public health threats in a timely manner. These functions are often difficult and require international cooperation given the rapidity with which diseases cross national borders and spread throughout the global community as a result of travel and migration by both humans and animals. As part of the U.S. Armed Forces Health Surveillance Center (AFHSC), the Department of Defense's (DoD) Globa Emerging Infections Surveillance and Response System (AFHSC-GEIS) has developed a global network of surveillance sites over the past decade that engages in a wide spectrum of support activities in collaboration with host country partners. Many of these activities are in direct support of International Health Regulations (IHR[2005]). The network also supports host country military forces around the world, which are equally affected by these threats and are often in a unique position to respond in areas of conflict or during complex emergencies. With IHR(2005) as the guiding framework for action, the AFHSC-GEIS network of international partners and overseas research laboratories continues to develop into a far-reaching system for identifying, analyzing and responding to emerging disease threats.